Migrasi dan Problematika Minoritas Muslim Thailand - Dian Ekawati (STAI ALHIKMAH Jakarta, 2019)
Migration is the movement of population from one area to another, whether from one village to other village or from one city to another city and from one country to other country conducted by someone or group of society with intention to stay and live or not, due to various factors as the reasons. Thailand is one of the country in Southeast Asian countries with its geographical location between Australian Continent and China’s mainland. Muslims in Thailand are minority that develop rapidly and the biggest minority after China. They live in the southern part of Thailand as the base of Malay-Muslim communities, but it is a region that has religious conflict. Thai government obliges assimilation of Thai culture (Buddhism) towards Muslim minority. The struggle of Muslim Pattani society takes place for the their freedom in worship and conserves Pattani Malay c ulture. Keywords: Migration, Cultural Assimilation, Minority Muslims Migrasi adalah perpindahan penduduk dari suatu wilayah ke wilayah lain baik itu dari desa ke desa lain, dari desa ke kota atau dari kota ke kota dan dari suatu negara ke negara lain yang dilakukan oleh seseorang atau sekelompok msyarakat dengan niat menetap atau tidak menetap karena berbagai faktor yang menjadi penyebabnya. Thailand adalah salah satu negara diantara negaranegara di kawasan Asia Tengara dengan letak geografisnya berada di kawasan antara Benua Australia dan daratan China. Umat Islam di Thailand merupakan minoritas yang berkembang cepat dan merupakan minoritas terbesar setelah China, Mereka tinggal di kawasan Thailand bagian selatan sebagai basis masyarakat Melayu-Muslim namun merupakan daerah konflik agama. Pemerintah Thailand mewajibkan asimilasi budaya Thai (agama Budha) kepada muslim minoritas. Perjuangan masyarakat Muslim Pattani terjadi demi kebebasan mereka dalam beribadah dan melestarikan budaya Melayu Pattani. Kata Kunci: Migrasi, Asimilasi Budaya, Muslim Minoritas